Postoperative complications and reduction of quality of life in elderly individuals after femur and hip fracture (Research, Society and Development, 2022)
Objective: To identify the influential factors in postoperative complications in femur and hip surgery in elderly patients. Methodology: This is an exploratory, descriptive study, of the type Integrative Literature Review, in which data were collected from the virtual research libraries: Online Electronic Scientific Library (SCIELO), Virtual Health Library (BVS), and Latin Literature American and Caribbean Health Sciences (LILACS). Results: Elderly patients who live more active lives have a faster recovery and decreased risk compared to elderly patients who are dependent on caretakers. Other influential factors in complications and postoperative recovery are the presence of comorbidities, dementia, UTI, and high risk of sepsis. Conclusion: A multidisciplinary team is needed to assist the patient and caregivers in preparing for hospital discharge and continuity of care at home, giving all the necessary information, thus solving doubts and fears, helping the patient so that he can achieve a better quality of life, independence and autonomy.